Regional wheat price effects of extreme weather events and wheat export controls in Russia and Ukraine; Regionale Weizenpreiseffekte von Wetterextremen und Weizenexportkontrollen in Russland und der Ukraine - Linde Götz; Ivan Djuric; Oleg Nivievskyi (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2016)
This paper further builds on the price transmission model framework of existing studies to identify domestic wheat price effects of wheat export controls. We explicitly take the fact into account that a harvest failure causes domestic price effects as well. Moreover, the analysis at the regional level provides further evidence of the functioning of export controls in a large country. Results suggest a pronounced regional heterogeneity in the strength of domestic price effects of the 2010/11 export ban in Russia. The wheat price dampening effects amount to up to 67 % and are strongest in the major wheat exporting region with direct access to the world market. This effect is transmitted to other regions by increased and reversed interregional trade flows. Contrasting, regional variation of export controls domestic price effects in Ukraine is rather small. – – Dieser Artikel entwickelt den Preistransmissionsansatz aus der Literatur weiter, um inländische Weizenpreiseffekte von Weizenexportkontrollen zu identifizieren. In unserem Ansatz findet speziell Berücksichtigung, dass auch Mißernten selbst Preiseffekte auslösen. Die Ergebnisse der Analyse auf regionaler Ebene weisen auf eine starke regionale Heterogenität bezüglich der Stärke der Preiseffekte während des Exportverbots 2010/11 in Russland hin. Der den Weizenpreis dämpfende Effekt ist in der Region mit direktem Zugang zum Weltmarkt am Stärksten und beläuft sich auf 67 %. Dieser Effekt wurde durch stark ansteigenden interregionalen Weizenhandel, zum Teil auch im Rahmen von Handelsumkehrung, in die übrigen Regionen übertragen. Im Unterschied zu Russland ist die Variation des inländischen Preiseffekts von Exportkontrollen in der Ukraine deutlich schwächer.
urn:nbn:de:gbv:3:2-54036
Keywords: C22; E30; Q11; Q17; Q18; 330; export controls; international trade; agricultural trade policy; Russia; Ukraine; grain markets; food security; extreme weather events; climate change; Exportkontrollen; internationaler Handel; Agrarhandel; Agrarhandelspolitik; Russland; Ukraine; Getreidemärkte; Ernährungssicherung; extreme Wetterereignisse; Klimawandel